2022
DOI: 10.1002/alz.12626
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia and mild cognitive impairment in indigenous Bolivian forager‐horticulturalists

Abstract: Introduction:We evaluated the prevalence of dementia and mild cognitive impairment (MCI) in indigenous Tsimane and Moseten, who lead a subsistence lifestyle. Methods: Participants from population-based samples ≥ 60 years of age (n = 623) were assessed using adapted versions of the Modified Mini-Mental State Examination, informant interview, longitudinal cognitive testing and brain computed tomography (CT) scans. Results: Tsimane exhibited five cases of dementia (among n = 435; crude prevalence = 1.2%, 95% conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“… Two-phase study ≥ 65 None (n = 25, %) 1–4 years (n = 108, %) 5–8 years (n = 139, %) 9 − 12 (n = 213, %) 13 + (n = 195, %) DSM-IV, ICD-10, NINCDS-ADRDA, NINDS-AIREN AVLT, VFT, MDRS, Matrix reasoning, digit span digit symbol-coding, comprehension, and vocabulary (WAIS-III) MMSE and FAQ 115 (16.9%) Custodio et al (2008) 2005 Peru (Lima) Urban 1532 Randomly selected from the region Three-phase study ≥ 65 Illiterates (n = 269, 17,5%) 1–3 years (n = 312, 20,4%) 4–7 years (n = 417,27,2%) 8 + (n = 534, 34,9%) DSM IV, NINCDS-ADRDA, NINDS-AIREN MMSE, CDT, AVLT, Logical Memory Subtest and Letter-Number (WAIS), TMT A and B, ROCF, BNT, WCST, DS, and CDR MMSE, CDT, PFAQ 103 (6.72%) Davis et al (2018) 2011 Trinidad Urban 1832 Randomly selected from electoral districts One-phase study ≥ 70 None (n = 139, %) Primary (n = 1231, %) Secondary (n = 253, %) Tertiary (n = 124, %) 10/66 dementia diagnosis algorithm/ DSM-IV CSI-D, CERAD 10-word list learning task, and Euro-D scale 442 (23.4%) Eldemire- Shearer et al (2018) 2012 Jamaica Unclear 301 Randomly selected from a national sample. One-phase study ≥ 60 DSM-IV MMSE and medical consensus 34 (11.41%) Gatz et al (2022) 2017 Bolivia (Tsimane and Moseten villages) Rural 604 ≥ 60 No formal education - Tsimane (80.6%) and Moseten (38.3%) DSM-V and NIA VS, DS, W R , VFT, SS, and SDT 6 (0.99%) Gooding et al (2006) 2003–2005 Colombia (Neiva) Urban 643 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Two-phase study ≥ 65 None (n = 25, %) 1–4 years (n = 108, %) 5–8 years (n = 139, %) 9 − 12 (n = 213, %) 13 + (n = 195, %) DSM-IV, ICD-10, NINCDS-ADRDA, NINDS-AIREN AVLT, VFT, MDRS, Matrix reasoning, digit span digit symbol-coding, comprehension, and vocabulary (WAIS-III) MMSE and FAQ 115 (16.9%) Custodio et al (2008) 2005 Peru (Lima) Urban 1532 Randomly selected from the region Three-phase study ≥ 65 Illiterates (n = 269, 17,5%) 1–3 years (n = 312, 20,4%) 4–7 years (n = 417,27,2%) 8 + (n = 534, 34,9%) DSM IV, NINCDS-ADRDA, NINDS-AIREN MMSE, CDT, AVLT, Logical Memory Subtest and Letter-Number (WAIS), TMT A and B, ROCF, BNT, WCST, DS, and CDR MMSE, CDT, PFAQ 103 (6.72%) Davis et al (2018) 2011 Trinidad Urban 1832 Randomly selected from electoral districts One-phase study ≥ 70 None (n = 139, %) Primary (n = 1231, %) Secondary (n = 253, %) Tertiary (n = 124, %) 10/66 dementia diagnosis algorithm/ DSM-IV CSI-D, CERAD 10-word list learning task, and Euro-D scale 442 (23.4%) Eldemire- Shearer et al (2018) 2012 Jamaica Unclear 301 Randomly selected from a national sample. One-phase study ≥ 60 DSM-IV MMSE and medical consensus 34 (11.41%) Gatz et al (2022) 2017 Bolivia (Tsimane and Moseten villages) Rural 604 ≥ 60 No formal education - Tsimane (80.6%) and Moseten (38.3%) DSM-V and NIA VS, DS, W R , VFT, SS, and SDT 6 (0.99%) Gooding et al (2006) 2003–2005 Colombia (Neiva) Urban 643 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding rurality, most of the studies included participants in urban areas ( n = 23), while two studies from Brazil ( Brucki and Nitrini, 2014 , Magalhães et al, 2008 ) and one from Bolivia ( Gatz et al, 2022 ) comprised individuals from rural populations, and eight studies had individuals recruited in both, rural and urban areas. In one article ( Soto-Añari et al, 2021 ), the rurality of the samples was unclear for the samples from all nine countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a recent study observed that the prevalence of dementia in the indigenous population of Tsimane and Moseten Amerindian of the Bolivian Amazon, who live a subsistence lifestyle, hunting, gathering food from the forest, and fishing, was one of the lowest compared with the majority population of the world. These observations evidence that a physically active lifestyle may be a critical factor in establishing improved body and brain health ( Gatz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
“…Mild cognitive impairment (MCI) is usually associated with cognitive impairment, which is seen with general age-related cognitive decline, but is not severe enough to lead to considerably impaired daily function (Stevens et al, 2022). Furthermore, the GRAPHICAL ABSTRACT | principal cognitive domain that could be afflicted refers to a decline in the capability to acquire raw information or recall stored information (Gatz et al, 2022;Kuroda et al, 2022). Clinically, age-related cognitive impairment represents the preclinical, transitional stage between healthy aging and dementia (Levey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%